INDIRECT EVIDENCE: MILD ALZHEIMER'S DISEASE & CANNABIS AFFECT THE SECOND STAGE OF FREE RECALL SUGGESTING LOCALIZATION IN HIPPOCAMPAL CA1 - Eugen Tarnow (Peoples' Friendship University of Russia (RUDN University), 2016)
Recently it was shown explicitly that free recall consists of two stages: the first few recalls empty working memory and a second stage, a reactivation stage, concludes the recall ([20]; for a review of the theoretical prediction see [15]). Here it is shown that the serial position curve changes in mild Alzheimer's disease (AD) and acute cannabis usage - lowered total recall and lessened primacy - are similar to second stage recall and different from working memory recall.Since cannabis and AD affect the second stage of free recall, the intersection of the two localizes the second stage of free recall to the CA1 area of the hippocampus. Since the second stage of recall uses a retrieval process that is accompanied by a linear rise in the error rate [18] this error generating mechanism should give clues to the structure of the corresponding neural network.